Overtreatment of men with early‐stage prostate cancer and limited life expectancy. Issue 23 (17th July 2014) - Danzig, Matthew R.; McKiernan, James M.
<x xml:space="preserve">Abstract</x> The accompanying article by Daskivich et al explores, with rigorous methodology, the issue of the overtreatment of men with early stage prostate cancer and limited life expectancy. Particular attention should be paid to the finding of the predominance of radiotherapy in this group, which should not be considered a benign alternative to surgery given the evidence for long‐term morbidity after this treatment.